EFL Need Analysis Among Eighth Graders: Aligning With 8 Dimensi Profil Lulusan - Utari, Zeli; Yovi, Febri Yonanda; Kardena, Absharini; Lismay, Leli (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
This research was conducted to identify the English learning needs of eighth-grade students at MTs Muhammadiyah Alamanda using the mixed method approach by integrating quantitative data from the questionnaire and qualitative data obtained from interviews. The questionnaire was designed with 15 questions answered by 20 participants based on the four-point Likert scale where 10 questions had validity scores above r-count > 0.444 and high reliability value of Cronbach's Alpha = 0.858. Based on the descriptive statistics, consistent positive scores were gained across all valid questions ranging between 3.35 to 3.75. The highest needs of students were found in the categories of corrective feedback from the teacher (M = 3.75), classroom atmosphere that is supportive (M = 3.75), and speaking skills required for social interactions (M = 3.70). It was further identified in the qualitative results gathered from interviews with teachers and students that the students preferred dynamic and interactive learning activities to passive ones. With the process of triangulation of both sets of data, the needs of the students have been analyzed in connection with the 8 Dimensi Profil Lulusan namely, Communication, Critical Thinking, Creativity, Collaboration, Independence, Citizenship, Health, and Faith & Piety.